Is democracy responsible for persistent corruption in some developing countries?: the case of Ghana - Asomah, Joseph Yaw (Crime, law and social change, 2024)
The question of whether democracy as a system of government helps combat corruption is a subject of debate, particularly in developing countries where democracy is practiced. The objective of this article is to answer a fundamental question: Should democracy be blamed for corruption in Ghana’s Fourth Republic? In addressing this question, this article uses interviews, media reports, Ghana’s constitution, relevant governance indices, and scholarly literature to argue that if constitutionalism and the rule of law, vital to democratic governance, are not respected, democracy cannot be blamed for the persistent corruption in Ghana. Hence, for democracy to help curb corruption, citizens—mainly the power elite—must take a keen interest in promoting constitutionalism and the rule of law. Based on the Ghanaian case, this article contributes to the ongoing debate on the relationship between democracy and corruption, especially in the sub-Saharan African context.